EBP50 suppresses the proliferation of MCF-7 human breast cancer cells via promoting Beclin-1/p62- mediated lysosomal degradation of c-Myc - LIU Hong; ZHAO Wu-li; WANG Jia-ping; XIN Bing-mu; SHAO Rong-guang (Acta Pharmacologica Sinica, 2018)
c-Myc, a key activator of cell proliferation and angiogenesis, promotes the development and progression of breast cancer. Ezrin-radixin-moesin-binding phosphoprotein-50 (EBP50) is a multifunctional scaffold protein that suppresses the proliferation of breast cancer cells. In this study we investigated whether the cancer-suppressing effects of EBP50 resulted from its regulation of c-Myc signaling in human breast cancer MCF-7 cells in vitro and in vivo. We first found a significant correlation between EBP50 and c-Myc expression levels in breast cancer tissue, and demonstrated that EBP50 suppressed cell proliferation through decreasing the expression of c-Myc and its downstream proteins cyclin A, E and Cdc25A in MCF-7 cells. We further showed that EBP50 did not regulate c-Myc mRNA expression, but it promoted the degradation of c-Myc through the autophagic lysosomal pathway. Moreover, EBP50 promoted integration between c-Myc and p62, an autophagic cargo protein, triggering the autophagic lysosomal degradation of c-Myc. In EBP50-silenced MCF-7 cells, activation of autophagy by Beclin-1 promoted the degradation of c-Myc and inhibited cell proliferation. These results demonstrate that the EBP50/Beclin-1/p62/c-Myc signaling pathway plays a role in the proliferation in MCF-7 breast cancer cells: EBP50 stimulates the autophagic lysosomal degradation of c-Myc, thereby inhibits the proliferation of MCF-7 cells. Based on our results, promoting the lysosomal degradation of c-Myc might be a promising new strategy for treating breast cancer.